A HIBRIDIZAÇÃO DE UM SISTEMA DE PRODUÇÃO: O CASO DA FÁBRICA DE AUTOMÓVEIS DAIMLERCHRYSLER DE JUIZ DE FORA - Sampaio, Paulo Soares (2006)
Faced with the challenges of a very competitive environment, the global automotive industry has tried to improve its work organization. Several models have been implemented in the 20th Century to manage production, and in the 80 s and 90 s, the Toyota Production System has turn to be the paradigm, that, according to Womack et al. (1992) would be the best way to organize production in the 21st century. Several researchers disagree, proposing that there is not a one best way , but several strategic paths that emerge in industries as responses according to each environment where they are present. According to Boyer and Freyssenet, among other authors, production systems hybridize, assuming new characteristics according to profit strategies adopted in the several political, economical and social environments. This work uses Boyer and Freyssenet´s model to analyze the adequacy of the Mercedes-Benz Production Model in the plant of Juiz de Fora and the need of hybridization of production system elements according to the perception of workers and managers of the plant, proposing changes to adapt Mercedes-Benz Production System to the plant needs.